Peran Keluarga Dalam Pembentukan Mental dan Pengaruhnya terhadap Perkembangan Kognitif pada Anak - Nasution, Fauziah; Eka Putri, Junita Hanum; Salsabila, Mutiara; Apriansyah, Andika (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article aims to reveal the importance of parental awareness in understanding children's growth and development. Parents are the first madrasah and teachers are the second education for early childhood. This research is a descriptive qualitative research in the form of a case study. Data obtained by means of observation and interviews with parents and teachers. The results of the study are the role of parents in stimulating children's cognitive development, namely as: ( observer, motivator, facilitator, madrasah, and problem server ); the second is the impact of the role of parents on children's cognitive development, namely: children are motivated to study at home, children become more critical, become more active, experience an increase in the achievement of learning outcomes, are able to set goals, and are able to bring up a character of responsibility and self-confidence. Keywords: Cognitive Development, Early Childhood